Cytotoxic CD4 T Cells—Friend or Foe during Viral Infection? - Juno, Jennifer A.; van Bockel, David; Kent, Stephen J.; Kelleher, Anthony D.; Zaunders, John J.; Munier, C. Mee Ling (Frontiers in Immunology, 2017)
CD4 T cells with cytotoxic function were once thought to be an artefact due to long term in vitro cultures but have in more recent years become accepted and reported in the literature in response to a number of viral infections. In this review we focus on cytotoxic CD4 T cells in the context of human viral infections and in some infections that affect mice and non-human primates. We examine the effector mechanisms used by cytotoxic CD4 cells, the phenotypes that describe this population, and the transcription factors and pathways that lead to their induction following infection. We further consider the cells that are the predominant targets of this effector subset, and describe the viral infections in which CD4 cytotoxic T lymphocytes have been shown to play a protective or pathologic role. Cytotoxic CD4 T cells are detected in the circulation at much higher levels than previously realised and are now recognised to have an important role in the immune response to viral infections.